Will This Help Be Helpful? Giving Aid to Strangers in the United States and Japan - Niiya, Yu; Handron, Caitlin; Markus, Hazel Rose (Frontiers in Psychology, 2022)
Japanese rank among the least likely to intervene to help a stranger in a non-emergency situation while Americans rank among the most likely. Across four studies, we demonstrate that Japanese are less likely to offer help to strangers because their decisions rely more heavily on the assessment of the needs of others. Accordingly, when there is uncertainty about the need for help, Japanese are less likely to intervene than Americans because without an understanding of the needs of recipient, the impact of intervention may also be harmful. When the situation is unambiguous, Japanese and Americans are equally likely to help. This divergence in readiness to help strangers elaborates the understanding of why people in Japanese contexts are more likely than those in U.S. contexts to attend to the situation and to avoid uncertain situations. It also illuminates cultural differences in models of agency—implicit understandings of when and why a person should act to aid another.